An adverse event following 2009 H1N1 influenza vaccination: a case of acute disseminated encephalomyelitis - Sang Teak Lee; Young June Choe; Won Jin Moon; Jin Woo Choi; Ran Lee (Korean Pediatric Society, 2011)
Acute disseminated encephalomyelitis (ADEM) is an inflammatory demyelinating disease of the central nervous system that typically follows an infection or vaccination and has a favorable long-term prognosis. We describe the first reported case of ADEM after vaccination against novel influenza A (H1N1). A previously healthy 34-month-old boy who developed ADEM presented with a seizure and left-sided weakness 5 days after vaccination against novel influenza A (H1N1). Cerebrospinal fluid examination revealed elevated cell counts. T2-weighted images and fluid-attenuated inversion recovery images revealed multiple patchy hyperintense lesions in the frontal and parietal subcortical white matter and the left thalamus. After the administration of intravenous corticosteroid, the patient's clinical symptoms improved and he recovered completely without neurologic sequelae.